Mathematical Methods and Algorithms for Improving Near-Infrared Tunable Diode-Laser Absorption Spectroscopy - Tianyu Zhang; Jiawen Kang; Dezhuang Meng; Hongwei Wang; Zhengming Mu; Meng Zhou; Xiaotong Zhang; Chen Chen (Sensors, 2018)
Tunable diode laser absorption spectroscopy technology (TDLAS) has been widely applied in gaseous component analysis based on gas molecular absorption spectroscopy. When dealing with molecular absorption signals, the desired signal is usually interfered by various noises from electronic components and optical paths. This paper introduces TDLAS-specific signal processing issues and summarizes effective algorithms so solve these.